On Imported and Domestic Human Papillomavirus Vaccines: Cognition, Attitude, and Willingness to Pay in Chinese Medical Students - Zhou, Liangru; Gu, Baiyang; Xu, Xiaoxue; Li, Yue; Cheng, Pengxin; Huo, Yue; Liu, Guoxiang; Zhang, Xin (Frontiers in Public Health, 2022)
This study aimed to analyze the cognition, attitude, and willingness to pay (WTP) for imported and domestic human papillomavirus (HPV) vaccines in Chinese medical students. Methods Medical students in Eastern, Central and Western China were investigated. We used the HPV cognitive list to measure the cognition of participants and implemented contingent valuation method (CVM) to value WTP. Tobit model was used to analyze the factors associated with WTP. Results The participants' average score for the 21 cognitive questions was 13.05 (±5.09). Among the participants, 60.82 and 88.01% reported that they would wish to be vaccinated and support the partners to be vaccinated. In addition, 92.54% (670) of the participants were willing to pay for HPV vaccines, at mean values (in RMB) of 1,689.80 (±926.13), 2,216.61 (±1190.62), and 3,252.43 (±2064.71) for imported bivalent, quadrivalent, and 9-valent vaccines, respectively, and at 910.63 (±647.03), 1,861.69 (±1147.80), and 2,866.96 (±1784.41) for their domestic counterparts, respectively. The increase in cognitive score has a positive effect on the WTP for imported vaccines (P < 0.05). Conclusions Most of the participants were likewise willing to receive the HPV vaccines. Their perceptions of the HPV vaccines valent and origin may affect their willingness to be vaccinated and pay for the vaccines. Increasing awareness of the HPV vaccines and the inclusion of the HPV vaccines in a Medicare reimbursement policy or immunization program could increase the coverage of the HPV vaccine.